Integrasi teknologi dalam meningkatkan efektivitas pembelajaran di pendidikan agama islam Di perguruan tinggi - Atabik Luthfi (Universitas Indraprasta PGRI, 2025)
Using technology in the learning process is crucial for creating a more interactive, flexible, and relevant learning experience that meets the current needs. The use of digital learning media, e-learning platforms, and technology-based applications allows for the delivery of more varied Islamic Religious Education materials and supports collaborative learning between lecturers and students. This study shows that technology integration not only increases access to educational resources but also enriches the learning experience through various innovative learning methods, such as gamification and the use of artificial intelligence (AI). This study uses a descriptive qualitative method with a case study approach at the Islamic University of Jakarta. The purpose of this study is to increase the effectiveness of technology integration in Islamic religious education education in universities so that it can support more innovative, inclusive, and relevant learning to the times. Research shows that technology integration in Islamic Religious Education learning in universities has great potential to increase the effectiveness of the learning process. However, there needs to be an increase in infrastructure and digital literacy to maximize the benefits that can be generated.